PELAKSANAAN PERIZINAN TENAGA KERJA ASING MELALUI PELAYANAN TERPADU SATU PINTU DI DAERAH (THE IMPLEMENTATION OF THE FOREIGN LABOR PERMITS THROUGH THE REGIONAL ONE STOP INTEGRATED SERVICES) - Monika Suhayati (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2017)
The utilization of the foreign labors and its licenses in Indonesia is regulated in Law No. 25 year 2007 regarding The Investment and Law No. 13 year 2003 regarding The Labor and its implementing regulations. The permits of the foreign labor is one of the licensing processed through the One Stop Integrated Services (PTSP). This licensing process is conducted in two stages, known as the stage of Foreign Labor Utilization Plan and the stage of Licensing the Foreign Labor. This paper is made to study the urgency of foreign labor licensing through One Stop Integrated Services, the regulation of foreign labor working permits through One Stop Integrated Services, and the effectiveness of the implementation of foreign labor working permits through the regional One Stop Integrated Services. The problem is analyzed using the principle of legality, delegation of authority, and the effectiveness of law enforcement. As the result of this study, the urgency of the foreign labor work licensing conducted through One Stop Integrated Services is to create the simplification and acceleration of the foreign labor working permits completion which will increase the investment. Based on the Presidential Regulation No. 97 year 2014, the implementation of One Stop Integrated Services by the regional government is carried out by the Provincial or Regency/Municipality Investment Body and One-Stop Integrated Services (BPMPTSP) based on the delegation of authority from the Governor or Head of Regent/Mayor to the Head of BPMPTSP of Provincial or Regency/ Municipality. In the implementation in some regions, there are problems such as The management of the issuance of the extension of Foreign Labor Utilization Permits which have not been transferred to the Provincial or Regency/Municipality One Stop Integrated Services: The Manpower Office at the provincial level has not yet assigned its functional personnel to The Provincial or Regency/Municipality One Stop Integrated Services under the control operation mechanism. In conclusion, it is necessary to revise the authority of the issuance of Foreign Labor Utilization Permits at the provincial/regency/municipality level, improve the coordination between related sectors, increase socialization of the SPIPISE, the budgeting the improvement of the foreign labor working permit facilities and infrastructure at the provincial/regency/ municipality One Stop Integrated Services, and improve the performance of the investment officers.ABSTRAKPenggunaan tenaga kerja asing (TKA) dan perizinannya di Indonesia diatur dalam UndangUndang Nomor 25 Tahun 2007 tentang Penanaman Modal dan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan beserta peraturan pelaksanaannya. Perizinan penggunaan TKA merupakan salah satu perizinan yang dilakukan melalui Pelayanan Terpadu Satu Pintu (PTSP). Perizinan tersebut dilakukan melalui dua tahap, yaitu tahap proses Rencana Penggunaan Tenaga Kerja Asing dan proses Izin Menggunakan Tenaga Kerja Asing (IMTA). Tulisan ini 56 NEGARA HUKUM: Vol. 8, No. 1, Juni 2017 hendak mempelajari urgensi perizinan TKA di PTSP, pengaturan perizinan TKA melalui PTSP, dan efektivitas pelaksanaan perizinan TKA melalui PTSP di daerah. Permasalahan dianalisa menggunakan asas legalitas, delegasi kewenangan, dan efektivitas penegakan hukum. Sebagai hasil dari kajian ini, urgensi perizinan TKA dilakukan di PTSP agar terciptanya penyederhanaan dan percepatan penyelesaian perizinan TKA yang akan meningkatkan investasi. Berdasarkan Peraturan Presiden Nomor 97 Tahun 2014 tentang Penyelenggaraan Pelayanan Terpadu Satu Pintu, penyelenggaraan PTSP oleh pemerintah daerah dilaksanakan oleh Badan Penanaman Modal dan Pelayanan Terpadu Satu Pintu (BPMPTSP) Provinsi atau Kabupaten/Kota berdasarkan pendelegasian wewenang dari gubernur atau bupati/walikota kepada Kepala BPMPTSP Provinsi atau Kabupaten/ Kota. Dalam pelaksanaannya di beberapa daerah, terjadi permasalahan antara lain pengurusan penerbitan perpanjangan IMTA yang belum dilimpahkan ke PTSP Provinsi atau Kabupaten/Kota, belum semua Dinas Tenaga Kerja Provinsi atau Kabupaten/Kota menugaskan tenaga fungsional di PTSP Provinsi atau Kabupaten/Kota dengan mekanisme Bawah Kendali Operasi. Sebagai kesimpulan, perlu dilakukan revisi pengaturan kewenangan penerbitan IMTA perpanjangan di tingkat provinsi atau kabupaten/kota, pembenahan koordinasi antarsektor terkait, peningkatan sosialisasi SPIPISE kepada masyarakat, penganggaran perbaikan sarana dan prasarana perizinan TKA di PTSP Provinsi atau Kabupaten/ Kota, pembenahan dan peningkatan kinerja aparat penanaman modal.